Neoplastic stenosis of hepaticojejunostomy with modified Barker technique: Transjejunal percutaneous endoscopic treatment: dilatation and endoprosthesis - Piazze, Alvaro; Henderson, Eduardo; Cagno, Carlos; Valiñas, Roberto (Cirugía del Uruguay, 1997)
Authors present the case of a 67 year old female patient who underwent hepaticojejunostomy due to cholangiocarcinoma, leaving it in subcutaneous location for future access (modified Berker's technique).